Analisis Kesulitan Guru dalam Mengembangkan CP, TP, dan ATP pada Modul Ajar di Sekolah Dasar - Enjang Yusup Ali; Dalia Susilawati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The Independent Curriculum in education provides freedom for students to learn independently, but teachers have obstacles related to the lack of knowledge of the independent curriculum because they do not have experience with the concept of the Independent Curriculum. In addition, the difference from the K-13 curriculum to the independent curriculum has resulted in problems experienced by some teachers in developing learning tools, namely that teachers have not been able to develop CP, TP, and ATP properly. Thus, this study aims to analyze the difficulties experienced by teachers when developing CP which is simplified into TP and developed into an ATP. This study used qualitative methods with data collection techniques using questionnaires. The questionnaire was given to grade 1,2, and grade 4,5 teachers who have used the Merdeka Curriculum in several schools in Sumedang Regency. Then, data analysis was carried out using the Miles and Huberman model which consists of three stages, namely data reduction, data presentation and conclusion drawing. Based on the results of the analysis, it shows that the total number of teachers who experience difficulties is 76 people or around 27.6% of the total 300 teachers, so efforts are needed to overcome teachers' difficulties in developing CP, TP, and ATP.